Efficient bioreductive production of (S)-N-Boc-3-hydroxypiperidine using ketoreductase ChKRED03. Issue 7 (July 2016) - Xu, Guang-Peng; Wang, Hai-Bo; Wu, Zhong-Liu
Graphical abstract: Highlights: Bioreduction of NBPO afforded the chiral intermediate of ibrutinib, ( S )-NBHP. The reaction was catalyzed with Ch KRED03 with excellent stereoselectivity. Using 3 g/L crude enzyme, 200 g/L substrate was completely reduced in 3 h. Abstract: Ibrutinib is an anticancer drug targeting B-cell malignancies. The key chiral intermediate for ibrutinib synthesis is the alcohol ( S )- N -Boc-3-hydroxypiperidine (( S )-NBHP), which can be produced via ketoreductase (KRED)-catalyzed bioreduction. After screening a small inventory of 27 KREDs mined from the genome of Chryseobacterium sp. CA49, Ch KRED03 was selected as the best performer, leading to the complete conversion of 100 g substrate/L within 10 h to yield ( S )-NBHP with high enantiomeric excess ( > 99% ee). The enzyme was NADPH dependent, and the highest enzymatic activity was observed at 30 °C in potassium phosphate buffer (pH 7.0). At a substrate/catalyst ratio of 66.7 (w/w), Ch KRED03 catalyzed the complete conversion of 200 g/L substrate within 3 h to yield ( S )-NBHP with >99% ee, demonstrating great potential for industrial application.